A heat-insulating energy-saving refractory castable and preparation method thereof
Through the synergistic effect of porous alumina aggregate and modified chopped zirconium-containing refractory fibers, the thermal insulation performance and mechanical strength of the thermal insulation refractory castable are improved, and the poor stability and thermal insulation effect in the prior art are solved. The best problem achieves efficient thermal insulation and thermal shock resistance, which is suitable for modern industrial environments.
Patent Information
- Application Number
- CN202411480159.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The existing heat-insulating refractory castables have problems such as poor stability, low strength, poor thermal insulation effect and easy cracking, which is difficult to meet the complex requirements of modern industry for refractory materials.
Using porous alumina aggregate, modified chopped zirconium-containing refractory fiber, coke gem fine powder, spodumene powder, cyanite powder, water reducing agent and dispersant combination, through high porosity, low thermal conductivity, modified fiber The pulling action, the synergistic action of sintering promoter and expansion agent improves the thermal insulation performance, mechanical strength and thermal shock stability of the castable.
It realizes the lightweight, high strength, excellent thermal insulation performance and thermal shock resistance stability of heat insulation insulation, meets the high-temperature environment needs of modern industry for refractory materials, and is simple in preparation, low in cost and environmentally friendly.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of refractory materials, and in particular to a heat-insulating and energy-saving refractory castable and a preparation method thereof. Background Art
[0002] Refractory castables are the most widely produced and used amorphous refractory materials, mainly used to construct various heating furnace linings and other integral structures. It is a granular and powdery material made of refractory substances, and a certain amount of binder and water are added to form it. It has high fluidity, is suitable for construction by pouring methods, and is an amorphous refractory material that can be hardened without heating. It is composed of refractory aggregates, powders, binders, admixtures, water or other liquid materials. It is generally cast and formed by pouring, vibrating or tamping at the site of use, and can also be made into prefabricated parts for use.
[0003] Refractory castables are a mixture of refractory aggregates, powders and binders, which are poured into the required form after adding water or other liquids for use. Refractory castables are used in special scenarios, such as heating furnaces and soaking furnaces in the steel industry, heat treatment furnaces in the machinery industry, thermal equipment such as petroleum, chemicals, nonferrous metals, and building materials, as well as thermal insulation linings and chimney linings. Therefore, the refractory structural layer is required to have good thermal insulation and fire resistance and high mechanical strength. Existing thermal insulation refractory castables have problems such as poor stability, low strength, poor thermal insulation effect, and easy cracking due to improper raw material selection and unreasonable particle matching.
[0004] Therefore, researching a thermal insulation and energy-saving refractory castable with excellent comprehensive performance has become a technical problem that technicians in this field need to solve urgently. Summary of the invention
[0005] The purpose of the present application is to provide a thermal insulation and energy-saving refractory castable and a preparation method thereof in view of the deficiencies in the current technology. The preparation method of the thermal insulation and energy-saving refractory castable of the present application has the advantages of simple preparation, low cost, energy saving and environmental protection. At the same time, the obtained thermal insulation and energy-saving refractory castable has light bulk density, high flexural strength, high compressive strength, and also has excellent thermal insulation performance and thermal shock resistance stability.
[0006] In the first aspect, the present application provides a heat-insulating and energy-saving refractory castable, which adopts the following technical solution:
[0007] A heat-insulating and energy-saving refractory castable comprises the following raw materials, measured by weight: 35-40 parts of porous alumina aggregate, 3-5 parts of modified chopped zirconium-containing refractory fibers, 8-10 parts of coke sapphire powder, 3-5 parts of kyanite powder, 5-6 parts of alumina powder, 2-3 parts of spodumene powder, 1-3 parts of a binder, 0.2-0.3 parts of a water reducer, and 0.2-0.3 parts of a dispersant.
[0008] By adopting the above technical solutions, porous alumina aggregate: as the main raw material, its high porosity and low thermal conductivity provide good thermal insulation performance for the castable. At the same time, its high compressive strength ensures the structural stability of the material. Modified short-cut zirconium-containing refractory fiber: through modification, the wettability with water and the dispersibility in the castable are improved, and the material is strengthened by its drawing effect, thereby improving the overall strength and toughness of the castable. Fine pyrotechnic stone powder: due to its excellent thermal shock stability and high temperature performance, it improves the comprehensive performance of the castable, especially in an environment with large temperature changes. Spodumene powder: as a sintering accelerator, it improves the sintering state of the castable under the conditions of use, promotes the formation of high-temperature ceramic bonding phase, and enhances the material's resistance to breakage. Kyanite powder: as an expansion agent, the volume expansion produced by its irreversible decomposition at high temperature offsets the volume contraction of the castable at high temperature, thereby preventing cracking. Water reducer: Through the combination of aliphatic high-efficiency water reducer and polycarboxylic acid high-performance water reducer, the construction fluidity of the castable is optimized, the amount of water added is reduced, and a high water reduction rate without segregation is achieved. Dispersant: The polysiloxane dispersant with a hyperbranched structure not only improves the water reduction, water seepage prevention, and easy exhaust properties of the castable, but also evenly combines the various components in the castable through its end group to form a whole, reducing the amount of water added and avoiding the impact on the mechanical properties of the castable. At the same time, the silica structure and boron-containing ceramic structure formed during the sintering process further enhance the thermal shock resistance of the material. In summary, the thermal insulation and energy-saving refractory castable in this application achieves light weight, high strength, excellent thermal insulation performance and thermal shock resistance through the precise proportioning and interaction of each component, meeting the requirements of modern industry for refractory materials.
[0009] Preferably, the method for preparing the porous alumina aggregate comprises the following steps:
[0010] S21, according to the mass fractions, gibbsite with an average particle size of 10 μm, boric acid, sodium carbonate, water glass with a mass concentration of 40%, and carbon powder with an average particle size of 10 μm are uniformly mixed, and then water is added and stirred for 1-2 hours to obtain a mixture;
[0011] S22, the mixture was transferred into a steel mold and compacted using a uniaxial press at 100 MPa to obtain a cylindrical compact with a diameter of 50 mm and a height of 50 mm, and then heated in a hydrogen reducing atmosphere at 1700°C for 2 h at a heating rate of 120°C / h. Subsequently, the cylindrical compact was heated in air at 1700°C for 1 h to burn off the residual carbon to obtain a porous alumina body;
[0012] S23, rolling the porous alumina body into coarse particles, sieving, and obtaining porous alumina aggregate with a particle size of 1-2 mm.
[0013] By adopting the above technical scheme, the role and synergy of the prepared porous alumina aggregate in the heat-insulating and energy-saving refractory castable are as follows: 1. Lightweight and high-strength: Through a specific preparation process, the porous alumina obtained has high porosity and low thermal conductivity, while maintaining a high compressive strength. This structure enables the final refractory castable to have high strength characteristics while maintaining light weight. 2. Improved thermal insulation performance: The high porosity and low thermal conductivity of porous alumina significantly improve the thermal insulation effect of the castable, enabling it to more effectively reduce heat transfer in a high temperature environment and protect the internal structure from high temperature damage. 3. Enhanced overall material performance: The porous alumina aggregate works together with other components (such as modified short-cut zirconium-containing refractory fibers, coke gemstone fine powder, etc.) to synergistically improve the overall performance of the castable through their respective unique properties. For example, the modified short-cut zirconium-containing refractory fibers enhance the toughness and flexural strength of the material, while the coke gemstone fine powder provides excellent thermal shock stability. 4. Promote sintering: The Na2O-B2O3-SiO2 liquid phase formed during the heating process promotes the growth of alumina plates. The porous alumina produced using high-temperature evaporation and heating at 1700°C has a "house of cards" structure made of highly anisotropic and crystallized alumina plate particles. This material shows high porosity, which is sufficient to resist the mechanical strength of the castable mix, and helps to improve the castable's resistance to breakage and overall stability. 5. Synergistic effect: The combination of porous alumina aggregates with other additives (such as spodumene powder, kyanite powder, etc.) further optimizes the performance of the castable. Spodumene powder, as a sintering promoter, improves the sintering condition of the castable, while kyanite powder, as an expansion agent, offsets the volume shrinkage at high temperatures and prevents cracking. In summary, porous alumina aggregate not only provides the basic characteristics of light weight and high strength in thermal insulation and energy-saving refractory castables, but also comprehensively improves the thermal insulation performance, mechanical strength, thermal shock stability and construction quality of the castables through synergistic effects with other ingredients, making it a high-performance refractory material.
[0014] Preferably, the mass ratio of gibbsite with an average particle size of 10 μm, boric acid, sodium carbonate, water glass with a mass concentration of 40%, and carbon powder with an average particle size of 10 μm is 100:1:0.4:1:10.
[0015] Preferably, the modification method of the modified short chopped zirconium-containing refractory fiber comprises the following steps:
[0016] S41, according to the mass fraction, adding 10 parts of nano-montmorillonite to 20 parts of 25% hydrochloric acid solution, treating at 120° C. for 1.5 h, collecting the precipitate by filtration, washing and drying to obtain modified montmorillonite;
[0017] S42. Add modified montmorillonite, short-cut zirconium-containing refractory fibers with a length of 5-10 mm, magnesium chloride and aluminum sulfate to a 6% sodium hydroxide aqueous solution according to their mass fractions. After ultrasonic dispersion for 1 hour, heat to 125°C under a nitrogen atmosphere for reaction for 20-24 hours. After drying, obtain modified short-cut zirconium-containing refractory fibers.
[0018] By adopting the above technical scheme, the modified short-cut zirconium-containing refractory fiber contains hydroxide that can form hydrogen bonds with water, thereby improving the wettability of the material and water. In addition, the modification improves the dispersibility of the short-cut zirconium-containing refractory fiber in the castable, and utilizes the strengthening and toughening effects generated by the drawing action of the fiber in the matrix to better improve the strength of the castable. At the same time, this modification method also helps to improve the thermal shock resistance and high temperature performance of the castable, thereby improving the comprehensive performance of the castable.
[0019] Preferably, the mass ratio of the modified montmorillonite, the short-cut zirconium-containing refractory fibers with a length of 5-10 mm, the magnesium chloride, the aluminum sulfate and the sodium hydroxide aqueous solution with a mass concentration of 6% is 1:4:11:12:150.
[0020] Preferably, the average particle size of the pyroxene fine powder is 0.5 mm, the average particle size of the kyanite powder is 180 mesh, the average particle size of the alumina micropowder is 5 μm, and the average particle size of the spodumene powder is 180 mesh.
[0021] Preferably, the binder is calcium aluminate cement, and the weight percentage of aluminum oxide in the calcium aluminate cement is 75%.
[0022] Preferably, the water reducer is prepared by mixing an aliphatic high-efficiency water reducer and a polycarboxylic acid-based high-performance water reducer in a mass ratio of 3:5.
[0023] By adopting the above technical scheme, the water reducer is prepared by mixing an aliphatic high-efficiency water reducer and a polycarboxylic acid-based high-performance water reducer in a mass ratio of 3:5. The role of the water reducer in this application is to improve the construction fluidity of the castable and reduce the amount of water added to the castable, so as to achieve the effect of both high water reduction rate and no segregation. Polycarboxylic acid-based high-performance water reducer has excellent water reduction rate, fluidity and permeability. Aliphatic high-efficiency water reducer: It can reduce the interaction between cement particles, improve the fluidity and strength of the castable, while reducing the number of bubbles and improving the durability of the castable. The synergistic effect between them can not only reduce the viscosity of the cement slurry and improve its fluidity, but also prevent the loss of water and maintain the consistency and fluidity of the slurry. This optimized combination avoids the performance shortcomings of a single water reducer, improves the construction fluidity of the castable, reduces the amount of water added to the castable, and achieves the effect of both high water reduction rate and no segregation.
[0024] Preferably, the method for preparing the dispersant comprises the following steps:
[0025] S91, dissolving 2.08 parts of tetraethoxysilane and 3.76 parts of dimethylchlorosilane in 60 parts of toluene according to their weight parts, and then reacting them at 65° C. for 6 hours under the catalysis of 0.02 parts of ferric chloride. After the reaction, the solvent was evaporated to obtain tetrakis(dimethylsilyl)siloxane;
[0026] S92, dissolving 3.28 parts of tetrakis(dimethylsilyl)siloxane and 36.6 parts of trimethoxysilane in 120 parts of toluene according to their mass fractions, adding 0.01 parts of tri(pentafluorophenyl)borane, reacting at 38° C. with stirring for 3 h, and then evaporating the solvent to obtain an alkoxy hyperbranched silicone resin;
[0027] S93. According to the mass proportions, 10 parts of alkoxy hyperbranched silicone resin and 1 part of trimethyl borate are added to a mixed solution consisting of 55 parts of ethanol and 40 g of water, and the mixture is stirred and hydrolyzed at 68° C. for 12 h to obtain a dispersant.
[0028] By adopting the above technical scheme, the prepared dispersant is an organic polymer material, which can improve the performance of the castable in terms of water reduction, easy exhaust, and micropore distribution in the matrix, meet the pumping construction process of the self-flowing castable, improve the construction fluidity of the castable, reduce the amount of water added to the castable, and improve the construction quality and comprehensive performance of the castable. The dispersant is specifically a polysiloxane dispersant with a hyperbranched structure, and each of its end groups can be used to evenly combine the various components in the castable to form a whole, so that there is no need to add too much water during the preparation of the castable, and the influence of the addition of excess water on the mechanical properties of the castable is prevented. At the same time, during the sintering process, the silicon oxygen segment in the main chain will form a silicon dioxide structure, which can be sintered with raw materials such as alumina to form a mullite structure. At the same time, the boron atoms in the borate group will form a boron-containing ceramic structure during the sintering process, so that its thermal shock resistance is further improved.
[0029] In a second aspect, the present application provides a method for preparing a heat-insulating and energy-saving refractory castable, which adopts the following technical solution:
[0030] The present application also provides a method for preparing the above-mentioned thermal insulating and energy-saving refractory castable, comprising the following steps: according to the mass fractions, porous alumina aggregate, modified chopped zirconium-containing refractory fiber, coke sapphire powder, kyanite powder, alumina powder, spodumene powder, binder, water reducer and dispersant are mixed and stirred evenly to obtain the thermal insulating and energy-saving refractory castable.
[0031] In summary, the beneficial technical effects of this application are:
[0032] 1. Improved thermal insulation performance: Through the use of porous alumina aggregate, the castable has higher porosity and low thermal conductivity, which significantly improves the thermal insulation effect. The porous structure can effectively reduce heat conduction, making the castable show good thermal insulation performance in high temperature environment.
[0033] 2. Enhanced strength and stability: The addition of modified short-cut zirconium-containing refractory fibers improves the overall strength and toughness of the material. This fiber is evenly dispersed in the matrix, and through the pulling action, it enhances the flexural strength and compressive strength of the castable, while improving the thermal shock resistance of the material.
[0034] 3. Improvement of sintering performance: The addition of spodumene powder promotes the sintering process at high temperature, improves the sintering state of the castable under the conditions of use, and improves the ability to resist breakage. As a sintering accelerator, spodumene powder helps to form a high-temperature ceramic bonding phase and enhance the durability of the castable.
[0035] 4. Prevent volume shrinkage and cracking: Kyanite powder, as an expansion agent, irreversibly decomposes at high temperatures to produce volume expansion, which offsets the volume shrinkage that may occur in the castable at high temperatures, thereby preventing cracking and ensuring the integrity and performance of the castable.
[0036] 5. Optimization of construction performance: The use of dispersant not only improves the water reduction, water prevention and easy degassing of the castable, but also improves the distribution of micropores, reduces the amount of water added, improves the construction fluidity, makes the castable easier to pump and construct, and improves the construction quality and comprehensive performance.
[0037] 6. Environmental protection and cost-effectiveness: The preparation method of the thermal insulation and energy-saving refractory castable is simple, low-cost, and has the characteristics of energy saving and environmental protection, which meets the requirements of current industrial sustainable development.
[0038] 7. Improvement of comprehensive performance: Through the reasonable proportion of the above raw materials and advanced preparation technology, the castable obtained not only has light bulk density and good thermal insulation performance, but also performs well in flexural strength, compressive strength and thermal shock stability, meeting the complex requirements of high-temperature industrial environment. DETAILED DESCRIPTION
[0039] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0040] In the following examples and preparation examples, 1 portion means 300 g.
[0041] Preparation Example 1 Preparation of porous alumina aggregate
[0042] The method for preparing porous alumina aggregate comprises the following steps:
[0043] S21, according to the mass proportions, 100 parts of gibbsite with an average particle size of 10 μm, 1 part of boric acid, 0.4 parts of sodium carbonate, 1 part of water glass with a mass concentration of 40%, and 10 parts of carbon powder with an average particle size of 10 μm were mixed evenly, and then water was added and stirred for 1.5 hours to obtain a mixture;
[0044] S22, the mixture was transferred into a steel mold and compacted using a uniaxial press at 100 MPa to obtain a cylindrical compact with a diameter of 50 mm and a height of 50 mm, and then heated in a hydrogen reducing atmosphere at 1700°C for 2 h at a heating rate of 120°C / h. Subsequently, the cylindrical compact was heated in air at 1700°C for 1 h to burn off the residual carbon to obtain a porous alumina body;
[0045] S23, rolling the porous alumina body into coarse particles, sieving, and obtaining porous alumina aggregate with a particle size of 1-2 mm.
[0046] Preparation Example 2 Preparation of modified short-cut zirconium-containing refractory fibers
[0047] The modification method of modified short-cut zirconium-containing refractory fiber comprises the following steps:
[0048] S41, according to the mass fraction, adding 10 parts of nano-montmorillonite to 20 parts of 25% hydrochloric acid solution, treating at 120° C. for 1.5 h, collecting the precipitate by filtration, washing and drying to obtain modified montmorillonite;
[0049] S42. According to the mass proportions, 10 parts of modified montmorillonite, 40 parts of short-cut zirconium-containing refractory fibers with a length of 5-10 mm, 110 parts of magnesium chloride and 120 parts of aluminum sulfate are added to 1500 parts of a 6% aqueous sodium hydroxide solution. After ultrasonic dispersion for 1 hour, the mixture is heated to 125°C under a nitrogen protective atmosphere for reaction for 22 hours. After drying, the modified short-cut zirconium-containing refractory fibers are obtained.
[0050] Preparation Example 3 Preparation of dispersant
[0051] The preparation method of the dispersant comprises the following steps:
[0052] S91, dissolving 2.08 parts of tetraethoxysilane and 3.76 parts of dimethylchlorosilane in 60 parts of toluene according to their weight parts, and then reacting them at 65° C. for 6 hours under the catalysis of 0.02 parts of ferric chloride. After the reaction, the solvent was evaporated to obtain tetrakis(dimethylsilyl)siloxane;
[0053] S92, dissolving 3.28 parts of tetrakis(dimethylsilyl)siloxane and 36.6 parts of trimethoxysilane in 120 parts of toluene according to their mass fractions, adding 0.01 parts of tri(pentafluorophenyl)borane, reacting at 38° C. with stirring for 3 h, and then evaporating the solvent to obtain an alkoxy hyperbranched silicone resin;
[0054] S93. According to the mass proportions, 10 parts of alkoxy hyperbranched silicone resin and 1 part of trimethyl borate are added to a mixed solution consisting of 55 parts of ethanol and 40 g of water, and the mixture is stirred and hydrolyzed at 68° C. for 12 h to obtain a dispersant. Example 1
[0055] A heat-insulating and energy-saving refractory castable comprises the following raw materials, measured by weight: 35 parts of porous alumina aggregate, 3 parts of modified chopped zirconium-containing refractory fibers, 8 parts of pyroxene fine powder (average particle size of 0.5 mm), 3 parts of kyanite powder (average particle size of 180 mesh), 5 parts of alumina micropowder (average particle size of 5 μm), 2 parts of spodumene powder (average particle size of 180 mesh), 1 part of binder, 0.2 parts of water reducer, and 0.2 parts of dispersant. The binder is calcium aluminate cement, in which the weight percentage of alumina is 75%, and the water reducer is prepared by mixing an aliphatic high-efficiency water reducer and a polycarboxylic acid-based high-performance water reducer in a weight ratio of 3:5.
[0056] The preparation method of the above-mentioned thermal insulating and energy-saving refractory castable comprises the following steps: according to the mass proportions, porous alumina aggregate, modified chopped zirconium-containing refractory fiber, coke sapphire powder, kyanite powder, alumina powder, spodumene powder, binder, water reducer and dispersant are mixed and stirred evenly to obtain the thermal insulating and energy-saving refractory castable. Example 2
[0057] A heat-insulating and energy-saving refractory castable comprises the following raw materials, measured by weight: 40 parts of porous alumina aggregate, 5 parts of modified short-cut zirconium-containing refractory fibers, 10 parts of coke sapphire powder (average particle size of 0.5 mm), 5 parts of kyanite powder (average particle size of 180 mesh), 6 parts of alumina micropowder (average particle size of 5 μm), 3 parts of spodumene powder (average particle size of 180 mesh), 3 parts of binder, 0.3 parts of water reducer, and 0.3 parts of dispersant. The binder is calcium aluminate cement, in which the weight percentage of alumina is 75%, and the water reducer is prepared by mixing an aliphatic high-efficiency water reducer and a polycarboxylic acid-based high-performance water reducer in a weight ratio of 3:5.
[0058] The preparation method of the above-mentioned thermal insulating and energy-saving refractory castable comprises the following steps: according to the mass proportions, porous alumina aggregate, modified chopped zirconium-containing refractory fiber, coke sapphire powder, kyanite powder, alumina powder, spodumene powder, binder, water reducer and dispersant are mixed and stirred evenly to obtain the thermal insulating and energy-saving refractory castable. Example 3
[0059] A heat-insulating and energy-saving refractory castable comprises the following raw materials, measured by weight: 38 parts of porous alumina aggregate, 4 parts of modified chopped zirconium-containing refractory fibers, 9 parts of pyroxene fine powder (average particle size of 0.5 mm), 4 parts of kyanite powder (average particle size of 180 mesh), 5.5 parts of alumina micropowder (average particle size of 5 μm), 2.5 parts of spodumene powder (average particle size of 180 mesh), 2 parts of a binder, 0.25 parts of a water reducer, and 0.25 parts of a dispersant. The binder is calcium aluminate cement, in which the weight percentage of alumina is 75%, and the water reducer is prepared by mixing an aliphatic high-efficiency water reducer and a polycarboxylic acid-based high-performance water reducer in a weight ratio of 3:5.
[0060] The preparation method of the above-mentioned thermal insulating and energy-saving refractory castable comprises the following steps: according to the mass proportions, porous alumina aggregate, modified chopped zirconium-containing refractory fiber, coke sapphire powder, kyanite powder, alumina powder, spodumene powder, binder, water reducer and dispersant are mixed and stirred evenly to obtain the thermal insulating and energy-saving refractory castable.
[0061] Comparative Example 1
[0062] The same as Example 3, except that an equal amount of porous CA6 (CaO·6Al2O3) aggregate with a particle size of 1-2 mm is used instead of the porous alumina aggregate.
[0063] Comparative Example 2
[0064] The same as Example 3, except that an equal amount of short-cut zirconium-containing refractory fibers with a length of 5-10 mm is used instead of the modified short-cut zirconium-containing refractory fibers.
[0065] Comparative Example 3
[0066] The same as Example 3, except that the amount of dispersant added is 0 parts.
[0067] Comparative Example 4
[0068] The same as Example 3, except that the water reducer is an aliphatic high-efficiency water reducer.
[0069] Comparative Example 5
[0070] The same as Example 3, except that the water reducer is a polycarboxylic acid-based high-performance water reducer.
[0071] Performance Testing
[0072] 5% water of the total mass of the castable was added to the heat-insulating and energy-saving refractory castables prepared in Examples 1 to 3 and Comparative Examples 1 to 5, respectively, the mixture was mixed and stirred, cast and molded, dried at 110°C for 24h, kept warm at 1500°C for 3h, and tested as follows. The test results are shown in Table 1.
[0073] Bulk density: refer to the liquid static weighing method of YB / T 5200-1993 "Test method for apparent porosity and bulk density of dense refractory castables" to test the bulk density;
[0074] Flexural strength: Refer to the method of GB / T 3001-2017 "Test method for flexural strength of refractory materials at room temperature" to test the flexural strength;
[0075] Compressive strength: refer to GB / T 5072-2008 "Test method for compressive strength of refractory materials at room temperature" to test the compressive strength;
[0076] Thermal conductivity: Refer to GB / T5990-2006 "Test method for thermal conductivity of refractory materials" to test the thermal conductivity.
[0077] Table 1 Performance test
[0078]
[0079] Analyzing the data in Table 1, we can see that:
[0080] 1) The heat-insulating and energy-saving refractory castables prepared in Examples 1 to 3 have light bulk density, high flexural strength, high compressive strength, and also have excellent heat-insulating properties and thermal shock resistance stability.
[0081] 2) The comparative analysis of the performance of the thermal insulation and energy-saving refractory castables prepared in Example 3 and Comparative Example 1 shows that the porous alumina aggregate prepared in the present application not only provides the basic characteristics of light weight and high strength in the thermal insulation and energy-saving refractory castable, but also comprehensively improves the thermal insulation performance, mechanical strength, thermal shock stability and construction quality of the castable through the synergistic effect with other components, making it a high-performance refractory material with better performance than the porous CA6 (CaO·6Al2O3) aggregate used on the market.
[0082] 3) The comparative analysis of the performance of the heat-insulating and energy-saving refractory castables prepared in Example 3 and Comparative Example 2 shows that the modified short-cut zirconium-containing refractory fibers contain hydroxides that can form hydrogen bonds with water, thereby improving the wettability of the material and water, and through modification, the dispersibility of the short-cut zirconium-containing refractory fibers in the castable is improved, and the strengthening and toughening effects generated by the drawing action of the fibers in the matrix are utilized to better improve the strength of the castable. At the same time, this modification method also helps to improve the thermal shock resistance and high temperature performance of the castable, thereby improving the comprehensive performance of the castable.
[0083] 4) The performance comparison analysis of the heat-insulating energy-saving refractory castables prepared in combination with Example 3 and Comparative Example 3 shows that the dispersant prepared in the present application is a polysiloxane dispersant with a hyperbranched structure, and each of its end groups can be used to evenly combine the various components in the castable to form a whole, so that there is no need to add too much water during the preparation of the castable to prevent the addition of excess water from affecting the mechanical properties of the castable. At the same time, during the sintering process, the silicon-oxygen segment in the main chain will form a silicon dioxide structure, which can be sintered with raw materials such as alumina to form a mullite structure. At the same time, the boron atoms in the borate ester group will form a boron-containing ceramic structure during the sintering process, so that its thermal shock resistance is further improved.
[0084] 5) The performance comparison analysis of the heat-insulating energy-saving refractory castables prepared in combination with Example 3 and Comparative Examples 4-5 shows that the water reducer is prepared by mixing aliphatic high-efficiency water reducer and polycarboxylic acid high-performance water reducer in a mass ratio of 3:5. The synergistic effect between them can not only reduce the viscosity of the cement paste and improve its fluidity, but also prevent the loss of water and maintain the consistency and fluidity of the paste. This optimized combination avoids the performance shortcomings of a single water reducer, improves the construction fluidity of the castable, reduces the amount of water added to the castable, and achieves the effect of high water reduction rate and no segregation, thereby improving the comprehensive performance of the castable.
[0085] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.
Claims
1. A heat-insulating and energy-saving refractory castable, characterized in that: The raw materials are composed of the following materials by weight: 35-40 parts of porous alumina aggregate, 3-5 parts of modified chopped zirconium-containing refractory fibers, 8-10 parts of coke sapphire powder, 3-5 parts of kyanite powder, 5-6 parts of alumina powder, 2-3 parts of spodumene powder, 1-3 parts of binder, 0.2-0.3 parts of water reducer, and 0.2-0.3 parts of dispersant; the preparation method of the porous alumina aggregate comprises the following steps: S21, according to the mass fractions, gibbsite with an average particle size of 10 μm, boric acid, sodium carbonate, water glass with a mass concentration of 40%, and carbon powder with an average particle size of 10 μm are uniformly mixed, and then water is added and stirred for 1-2 hours to obtain a mixture; S22, the mixture was transferred into a steel mold and compacted using a uniaxial press at 100 MPa to obtain a cylindrical compact with a diameter of 50 mm and a height of 50 mm, and then heated in a hydrogen reducing atmosphere at 1700°C for 2 h at a heating rate of 120°C / h. Subsequently, the cylindrical compact was heated in air at 1700°C for 1 h to burn off the residual carbon to obtain a porous alumina body; S23, rolling the porous alumina body into coarse particles, sieving, and obtaining porous alumina aggregate with a particle size of 1-2 mm; The modification method of the modified short-cut zirconium-containing refractory fiber comprises the following steps: S41, adding 10 parts of nano-montmorillonite to 20 parts of 25% hydrochloric acid solution by mass, treating at 120° C. for 1.5 h, collecting the precipitate by filtration, washing and drying to obtain modified montmorillonite; S42, adding modified montmorillonite, short-cut zirconium-containing refractory fibers with a length of 5-10 mm, magnesium chloride and aluminum sulfate to a sodium hydroxide aqueous solution with a mass concentration of 6% according to the mass fractions, ultrasonically dispersing for 1 hour, heating to 125° C. under a nitrogen atmosphere for reaction for 20-24 hours, and drying to obtain modified short-cut zirconium-containing refractory fibers; The water reducer is prepared by mixing an aliphatic high-efficiency water reducer and a polycarboxylic acid-based high-performance water reducer in a mass ratio of 3:5; The preparation method of the dispersant comprises the following steps: S91. Dissolve 2.08 parts of tetraethoxysilane and 3.76 parts of dimethylchlorosilane in 60 parts of toluene according to their weight fractions, and then react at 65° C. for 6 hours under the catalysis of 0.02 parts of ferric chloride. After the reaction is completed, evaporate the solvent to obtain tetrakis(dimethylsilyl)siloxane; S92, according to the mass fractions, 3.28 parts of tetrakis(dimethylsilyl)siloxane and 36.6 parts of trimethoxysilane were dissolved in 120 parts of toluene, 0.01 parts of tri(pentafluorophenyl)borane were added, and the mixture was reacted at 38° C. with stirring for 3 h, and the solvent was evaporated to obtain an alkoxy hyperbranched silicone resin; S93. According to the mass proportions, 10 parts of alkoxy hyperbranched silicone resin and 1 part of trimethyl borate are added to a mixed solution consisting of 55 parts of ethanol and 40 g of water, and the mixture is stirred and hydrolyzed at 68° C. for 12 h to obtain a dispersant.
2. A heat-insulating and energy-saving refractory castable according to claim 1, characterized in that: The mass ratio of gibbsite with an average particle size of 10 μm, boric acid, sodium carbonate, water glass with a mass concentration of 40%, and carbon powder with an average particle size of 10 μm is 100:1:0.4:1:
10.
3. The heat-insulating and energy-saving refractory castable according to claim 1, characterized in that: The mass ratio of the modified montmorillonite, the short-cut zirconium-containing refractory fiber with a length of 5-10 mm, magnesium chloride, aluminum sulfate and the sodium hydroxide aqueous solution with a mass concentration of 6% is 1:4:11:12:
150.
4. The heat-insulating and energy-saving refractory castable according to claim 1, characterized in that: The average particle size of the coke gemstone fine powder is 0.5 mm, the particle size of the kyanite powder is 180 mesh, the average particle size of the alumina micropowder is 5 μm, and the particle size of the spodumene powder is 180 mesh.
5. The heat-insulating and energy-saving refractory castable according to claim 1, characterized in that: The binder is calcium aluminate cement, and the weight percentage of aluminum oxide in the calcium aluminate cement is 75%.
6. A method for preparing a heat-insulating and energy-saving refractory castable according to any one of claims 1 to 5, characterized in that: The following steps are involved: Porous alumina aggregate, modified chopped zirconium-containing refractory fiber, coke sapphire powder, kyanite powder, alumina powder, spodumene powder, binder, water reducer and dispersant are mixed and stirred uniformly according to mass proportions to obtain a heat-insulating and energy-saving refractory castable.
